Pengaruh Komitmen Organisasi, Stres Kerja, dan Motivasi Kerja Terhadap Kinerja Driver Maxim di Bandar Lampung - Anasthasya Lynetta Widjaja; Iskandar Ali Alam (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The performance quality of the drivers has a significant impact on the quantity of Maxim performance, therefore the business must take these variables into account. This study aims to analyze the effect of organizational commitment, work stress, and work motivation on the performance of maxim online motorcycle taxi drivers in Bandar Lampung. 100 motorcycle riders maxim Bandar Lampung made up the sample in this study, which employed quantitative approaches. Coefficient of determination, partially test & simultaneous test, multiple linear regression models and hypothesis test are the analytical techniques research used. The research shows that the results of the conclusion that organizational commitment and work stress have no effect while work motivation has a significant positive effect on the performance of maxim online motorcycle taxi drivers in Bandar Lampung. While the F test has the result that’simultaneously the variables organizational commitment, work motivaton & job stress together have a significants effect on the performance of maxim online motorcycle taxi drivers in Bandar Lampung. The predictive capacity of those three variables on the overall performance of maxim online motorcycle taxi drivers in Bandar Lampung is 37,7%, whilst the final 62,3% is stimulated by other variable factors outside the regression version.